Mastering the Art of Chibi: A Comprehensive Review of “Beginner’s Guide to Drawing Manga Chibi Girls” - Aulia, Gina Fajri (KOLEKTIF: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
Book Title: Beginner’s Guide To Drawing Manga Chibi Girls: Create Your Own Adorable Mini Characters.Author: Mosoko Miyatsuki and Tsubara Kodomaru.Year: 2021Publisher: Tuttle Publishing.Number of Pages: 184 pages.  ISBN: 978-480-531-613-9The book consists of six chapters: 1. Let's Start with the Basics; 2. Character with a 2.5 Head-to-Body Ratio; 3. Drawing Characters with Different Head-to-Body Ratios; 4. Drawing Chibi Faces; 5. Expressing Chibi Emotions; and 6. Inside the Artist Studio.